(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Today‘s progressive man has become such as active factor that he became to earth as a heap of rubbish. And he wants more and more fame in capitalistic world for his progress. He is not aware for his new generation, animals and plants biological system. Man’s “Use and Throw” bad tendency make to our entire surrounding world pollute by different pollutant. We can see on everywhere that a great heap of rubbish that release to very dangerous gases and that effect to all biotic phenomenon direct or indirect way. Today we can see human wastes spreading as a non-biodegradable on Mt. Averts to oceanic trenches also.Today in our environment fluid and solid stage waste in being spread through various activities - agricultural waste, domestic waste, industrial waste and radioactive waste etc.Today some of the world’s developed countries on the basis of science, a pile of waste for human various domestic products have turned into a form of change and made them resources. From a pile of waste in a country like Netherlands find out the r Polder land a pile of waste. And lack of space and technology developed countries this problem is having a wild look.